RASIO KEUANGAN TERBAIK UNTUK MEMPREDIKSI NILAI PERUSAHAAN - Meythi Meythi (Jurnal Keuangan dan Perbankan, 2013)
This study aimed to determine the best financial ratios in predicting firm value. There were 12 financial ratios,Current Ratio, Quick Ratio, Debt Ratio, Equity to Total Asset, Equity to Total Liabilities, Equity to FixedAsset, Profit Margin, Return on Asset, Return on Equity, Fixed Assets Turnover, Total Asset Turnover, andMarket to Book Ratio categorized into five factors (solvability factor, liquidity factor, profitability factor,activity factor, and firm value factor) in predicting firm value. Data in this study were from manufacturingfirms listed on Indonesia Stock Exchange during 2007-2012. Factor analysis was used to determine the bestfinancial ratios in predicting firm value. The empirical result showed that Equity to Total Asset was the bestfinancial ratio in predicting firm value.